2020
DOI: 10.3390/nu12103104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Rehabilitation and Nutritional Intake Management on Improvement in Tongue Strength in Sarcopenic Patients

Abstract: The study aimed to investigate the impact of physical intervention and the amount of nutritional intake on the increase in tongue strength and swallowing function in older adults with sarcopenia. From November 2018 and May 2019, older patients with sarcopenia who were admitted for rehabilitation were analyzed. The intervention employed in the study was the usual physical and occupational therapy for two months. Tongue strength was measured before and after two months of treatment. Data on tongue strength, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Physical interventions may also affect muscle tissue throughout the body, including swallowing-related muscle groups [ 30 , 31 ]. Physical rehabilitation may be effective in improving swallowing ability [ 13 , 14 ]. Nagano et al [ 14 ] showed that physical rehabilitation was associated with a significant increase in tongue strength, a swallowing-related muscle group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Physical interventions may also affect muscle tissue throughout the body, including swallowing-related muscle groups [ 30 , 31 ]. Physical rehabilitation may be effective in improving swallowing ability [ 13 , 14 ]. Nagano et al [ 14 ] showed that physical rehabilitation was associated with a significant increase in tongue strength, a swallowing-related muscle group.…”
Section: Discussionmentioning
confidence: 99%
“…Physical rehabilitation may be effective in improving swallowing ability [ 13 , 14 ]. Nagano et al [ 14 ] showed that physical rehabilitation was associated with a significant increase in tongue strength, a swallowing-related muscle group. A combination of nutritional management and physical interventions is considered preferable for the treatment of systemic sarcopenia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations